Transnational Contexts of Culture, Gender, Class, and Colonialism in Play
XV, 218 p. 14 illus. in color.
Keywords: This book examines gamer culture, expressions of gender and class, and issues of colonialism and transnationalism in digital games in East Asia. Focusing on examinations of how video games and the universes they offer create complex hierarchies and unique, subversive interventions in East Asia, Lee and Pulos' volume critically examines how video games can shape cultural contexts and simultaneously react to the cultures that consume them. Contributions range from assessments the culture of game developer groups to representations of ethnicity in characters, with special attention paid to the glocalization of culture, including cultural adoption and adaption.